Diagnosis of Microbial Keratitis Causatives by Polymerase Chain Reaction - Ameen, Rasha S; Al-Shakarchi, Faiz I; Al-Shaibani, Abdulwahid B A (Al-Nahrain Journal of Science, 2018)
In order to evaluate the efficiency of using Polymerase Chain Reaction (PCR) in the identifications of microorganisms causing microbial keratitis, 20 corneal scraping samples were collected from patients who attended the Eye Casualty Unit at the Southampton General Hospital in the United Kingdom. Samples cultured on blood agar and chocolate agar incubated at 37 ͦ C for 24hrs and on sabrouad agar at 28 ͦC for one week. PCR procedure was performed with the primer paired that targeted to the 16S rRNA for bacterial species and 18S rRNA gene for fungal species, in addition to the species specific primer for the most common microbial keratitis causatives microorganisms. Results in the regards showed that out of the 20 presumed cases of keratitis, PCR showed positivity in 75% of them, from these 55% were due to the fungal infection and 20% of the cases indicated that the keratitis belonged to bacterial infections: In comparison, only 25% of positivity was obtained by the cultural method. The species specific primer showed that half of the 20% bacterial infection cases were caused by S. aureus and the other 10% referred to S.epidermidis infection. While the candida albicans primer gave a positive result only in 72% of the original percentage (55%), the rest 28% may belong to the other fungal infection. Depending on the above results, it can be concluded that PCR not only proved to be an effective rapid method for the diagnosis of bacterial and fungal keratitis, but was also more accurate and sensitive method than the culture methods.